(untitled) (diségno, 2026)
The volume La représentation des structures constructives by Adrian Gheorghiu and Virgil Dragomir [Gheorghiu, Dragomir 1968], the former an architect and the latter an engineer, was published in France in 1968 as a translation of a previous Romanian edition (fig. 1) [1]. It is a book that I regard as a working companion and, in a certain sense, a pivotal reference in my own education: for nearly twenty years it has accompanied my research, ever since I first studied it during my doctoral work at Sapienza University of Rome, where it served as an indispensable text for understanding the geometric nature of ruled surfaces. Over the years, I have come to appreciate that this work is not merely a technical manual; it is, rather, a true treatise on the profound relationship between form, structure, and representation, capable of speaking even today to architects, engineers, and scholars concerned with the logic of spatial configuration. [read more]